Peningkatan Keaktifan Belajar Matematika Kelas VI SD Pada Materi Operasi Hitung Bilangan Bulat Melalui Model Pembelajaran Kooperatif Tipe STAD - Setiyaningrum, Dewi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Less effective and innovative learning models are the factors causing the low activeness of learning mathematics. This study aims to increase the activeness of learning mathematics in sixth grade elementary school students on the material of integer arithmetic operations through the STAD type cooperative learning model. This type of research is Classroom Action Research (CAR). The research was conducted in two cycles. Data collection techniques: observation, test, documentation and field notes. The results showed that the use of the STAD type cooperative learning model was able to increase the activeness of learning mathematics in the class VI integer arithmetic operations material, namely (a) the activity of asking, answering and arguing in the pre-cycle 23%, the first cycle 53%, and the second cycle 83%. ; (b) active discussion in pre-cycle 30%, cycle I 63%, and cycle II 93%; and (c) the ability to work on pre-cycle questions 13%, cycle I 43%, and cycle II 77%. This study concludes that the STAD type cooperative learning model can increase the activeness of learning mathematics.